Prospective Multicenter Study on Subcutaneous Concentrated Desmopressin for Home Treatment of Patients with von Willebrand Disease and Mild or Moderate Hemophilia A - Rodeghiero, Francesco; Castaman, Giancarlo; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1996)
Desmopressin is the treatment of choice in most patients with von Willebrand disease (vWD) and mild hemophilia A (HA). Several studies have demonstrated that the intravenous and subcutaneous route of administration are equivalent in terms of pharmacokinetics and clinical efficacy. Home therapy of vWD and mild HA is desirable but so far there have been only a few case reports and no prospective studies. We report the results of a prospective study of home therapy in patients with vWD and mild-moderate HA using concentrated desmopressin self-administered subcutaneously. Clinical efficacy and safety were assessed by the patient using a questionnaire and direct interview. The patients were instructed on self-administration and dosage, reasons for treatment, recognition of side effects and recording clinical efficacy. The study lasted 12 months (range 6-17). During this time, 43/100 (43%) of the enrolled vWD patients (median basal VIII: C 24%, range 9-49) and 36/69 (52%) of HA patients (median basal VIII: C 10%, range 5-34) self-administered the drug. A total of 127 bleeding episodes requiring treatment occurred in patients with vWD and 92 in HA patients. There were 10 treatment failures of which 7 required in-hospital treatment. Overall, in 94% of treatments (excluding menorrhagia) the response was scored as excellent or good. In 86% of treated episodes of menorrhagia the response was scored as excellent or good. According to the patients, 81% of clinical situations would have required in-hospital treatment. Mild flushing, with or without headache, was the only consistent side-effect, reported in about 30% of treatments. In conclusion, home therapy with subcutaneous desmopressin for von Willebrand disease and hemophilia A was well accepted by the patients and proved feasible, efficacious and safe for the prevention or prompt treatment of bleeding.